A comparison between primary endorectal pull-through and staged procedures for patients with Hirschsprung's disease - Reda Zbaida; Corné de Vos; Daniel Sidler (EL-Med-Pub, 2021)
Background: Primary endorectal pull-through is becoming a standard of care across the globe. This study was done to compare the outcome of patients with Hirschsprung's disease (HD) who underwent primary endorectal pull-through with patients who were treated with a staged approach. Methods: A retrospective data review was done of all patients diagnosed with Hirschsprung's disease (HD) at Tygerberg Children's Hospital, a tertiary hospital in Cape Town, during an 11-year period (2007 - 2018).  The patients were divided into 2 groups: the primary Endorectal pull-through (ERP) group and the staged group and the two groups were compared.  Results: Eighty patients with histologically confirmed Hirschsprung's disease (HD) were seen at our institution during the study period (2007 - 2018). Four patients did not meet the inclusion criteria and were excluded. Of the remaining seventy-six who were included, forty-six patients (60.5%) had a primary endorectal-pull through (Primary group) and thirty patients (39.5%) had staged procedures (Staged group) with a stoma before the final ERP. The peri-operative complications were subdivided into major and minor complications. Minor perioperative complications in the primary group were less (13%) compared to the staged group (33%) with a p-value of 0.017, making the difference statistically significant. Anastomotic strictures were the most common complication in both groups with abdominal wound infection being more common in the staged group. The late complications were similar in both groups with a p-value of 0.43. Constipation was the most common complication in both groups, followed by soiling.  Conclusion: The two groups had a similar outcome without statistically significant differences. We can safely conclude that the primary endorectal pull-through for HD is at least as safe as the staged approach in Sub- Saharan Africa. With this technique, we avoid a stoma and the necessity for two surgical procedures with added potential complications.